A study of some Irish Lower Carboniferous fish microvertebrates - Duncan, Margaret (Trinity College (Dublin, Ireland). Department of Geology, 2000)
Fish microvertebrates (often referred to as ichthyoliths) are a common, but largely unrecorded, component of the faunas of the Irish Lower Carboniferous. Material from four study areas within the Dinantian (Carboniferous) of Ireland were studied with the aims of describing and illustrating the fish microvertebrates obtained from acid insoluble residues of limestones. The four study areas were Lyraun Cove, Hook Head, County Wexford (mixed carbonate/siliciclastic inner shelf; Tournaisian, Hastarian (Polygnathus inornatus conodont Biozone)); Urlingford, County Kilkenny (carbonate shelf, deeper, middle to outer part; Tournaisian, Ivorian (Polygnathus mehli conodont Biozone)); Kilbride, County Meath (Carbonate shelf, middle part; Ivorian, probably Freyrian (Polygnathus mehli conodont Biozone)); and Moyola River, Draperstown, County Londonderry (sabhka/tidal flat; probably Tournaisian, Freyrian (Pu miospore Biozone)). The fish microvertebrates, commonly less than 2mm in overall dimension, are made up of disarticulated teeth and scales/denticles of chondrichthyan fish together with teeth, scales/denticles and bone fragments of osteichthyan and acanthodian fish. The fish microvertebrates are described using a form of open nomenclature at generic level. They are illustrated by computer generated plates from original photographs taken using the scanning electron microscope. There are many taxonomic problems inherent in describing disarticulated material in terms of the Linnean Binomial System.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin